2018
DOI: 10.1007/s00436-018-6000-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation and risk factor analysis of Cryptosporidium spp. in calves from Italy

Abstract: To provide up-to-date information on the occurrence of Cryptosporidium in pre-weaned calves from Sardinia (Italy), the species implicated and their zoonotic potential, 147 faecal samples from 22 cattle herds were microscopically examined for Cryptosporidium oocysts; positive isolates were molecularly characterised. A questionnaire was developed to identify risk factors for Cryptosporidium infection. Overall, the percentage of positive calves and farms was 38.8 and 68.2%, respectively. The SSU rRNA-based PCR id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
40
4
6

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 58 publications
15
40
4
6
Order By: Relevance
“…All of the sequenced Cryptosporidium samples were confirmed as C. parvum subtype family IIa, which is in accordance with results from other countries as Canada [27], USA [28], England [29], Spain [25], New Zealand [30], Italy [31] and Germany [58]. Subtype family IId, common in Italian calves [31], was not detected in the present study. Specifically, 82.9% of the sequenced samples revealed C. parvum subtype IIaA15G2R1, the most prevalent subtype in calves worldwide [32,58].…”
Section: Discussionsupporting
confidence: 92%
“…All of the sequenced Cryptosporidium samples were confirmed as C. parvum subtype family IIa, which is in accordance with results from other countries as Canada [27], USA [28], England [29], Spain [25], New Zealand [30], Italy [31] and Germany [58]. Subtype family IId, common in Italian calves [31], was not detected in the present study. Specifically, 82.9% of the sequenced samples revealed C. parvum subtype IIaA15G2R1, the most prevalent subtype in calves worldwide [32,58].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to results from China (Cai et al, 2017;Feng and Xiao, 2017), the occurrence of this zoonotic IId family group in calves is rare in Europe and seems likely to have spread from Western Asia to other regions including France (Wang et al, 2014). This subtype family was described in European countries, such as in calves from Italy (Díaz et al, 2018), Belgium (Geurden et al, 2007), but never previously reported in France. Thus, the present study is the first to report the presence of the IId subtype in French calves.…”
Section: Discussioncontrasting
confidence: 68%
“…However, most of these studies relied on microscopic examination of fecal specimens. Cryptosporidium infection rates in Europe have been reported as follows: 38.8% of calves in Italy [3], 37% and 12% of dairy and beef calves, respectively, in Belgium [37], 36.7% of calves in Sweden [38], 22.5% of calves in Poland [39], 19.2% of lambs and 37.1% of goats in Poland [12], 74.4% of lambs and 93.8% of goat kids in Spain [11], 13.1% of lambs and 9.5% of goat kids in Belgium [40], and 5.1% of lambs and 7.1% of goat kids in Greece [10]. From these studies, it is clear that cryptosporidial infections are widespread in calves, lambs, and goat kids in Europe, including Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidium parvum has a number of subtypes that can be grouped into subtype families as measured by gp60 sequence analyses [2]. Healthy and diarrheic calves less than one month of age may facilitate the transmission of cryptosporidiosis in both humans and animals [3]. Other livestock are also potential reservoirs of this protozoan.…”
Section: Introductionmentioning
confidence: 99%